Massive rectal bleeding after prostate biopsy controlled by endoclipping in a patient using acetylsalicylic acid - (:unkn) unknown (CANADIAN UROLOGICAL ASSOCIATION, 2013)
A case of severe rectal bleeding following transurethral ultrasound (TRUS)-guided prostate biopsy is reported. Rectal bleeding is considered a minor, transient complication of this standard diagnostic procedure that can usually be controlled successfully by conservative measures. In this case where the patient had been taking acetylsalicylic acid (ASA), massive bleeding required hospitalization and blood transfusions. Conservative treatment attempts were not succesful, and profuse rectal bleeding was eventually treated by colonoscopy and endoclipping of the bleeding vessel. Although generally regarded as a less significant complication, rectal bleeding may rarely be encountered as a life-threatening situation. Furthermore, conservative therapeutic approach to this minor complication may be ineffective in patients taking ASA. Early endoscopic intervention may be necessary to prevent blood transfusion and prolonged hospitalization in severe rectal bleeding after TRUS biopsy.